Network traffic behaviour profiling - Piskozub, M (2020)
Nowadays, computer networks have become incredibly complex due to the evolution of online services and the rapid growth of the number of smart devices such as smartphones, tablets and laptops. Most of users’ information, even the most sensitive ones, are transmitted over the Internet. Unfortunately, due to this phenomenon we also see an increasing interest of malware developers who are able to find and exploit novel vulnerabilities in network devices to carry out their malicious intents. To tackle these threats, network analysts should be aided with advanced techniques to identify malicious traffic in order to guarantee the security of networks.